Viscum meyeri (Viscaceae)—a new name for Viscum anceps, an old-established mistletoe species endemic to southern Africa - Sosnovsky, Yevhen; Krasylenko, Yuliya; Nachychko, Viktor (Phytotaxa, 2021)
In this paper, we propose a new replacement name “Viscum meyeri” for a southern African endemic species currently known as V. anceps E.Mey. ex Sprague. The latter name is unavailable for use, being illegitimate as a later homonym of V. anceps Spreng.—the basionym for the presently accepted name Phoradendron anceps (Spreng.) M.Gómez. In addition, the second-step lectotypification of the new and replaced names is conducted. One collection from K is designated here as a lectotype of V. meyeri (≡ V. anceps E.Mey. ex Sprague), and eight more collections from FR, HAL, HBG, K, P, and S are considered as isolectotypes.